Optimization of Business Administration in Maritime Logistics Chain - Dirhamsyah; Eddi Suprayitno (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Belawan Port plays a strategic role in Indonesia’s maritime logistics chain, yet its business administration system continues to face inefficiencies due to fragmented digital infrastructure and poor inter-agency coordination. This study aims to analyze the current administrative challenges at Belawan Port and propose strategies for optimizing business processes through digital transformation and stakeholder integration. A qualitative descriptive method was employed, using semi-structured interviews, participatory observations, and documentation analysis in 2024. Informants included stakeholders from Pelindo, PT Belawan New Container Terminal, Customs, Quarantine, and logistics companies. Thematic analysis revealed three major challenges: incomplete digitization of the Terminal Operating System (TOS), persistent administrative bottlenecks due to manual validation, and a lack of cross-agency collaboration. Despite a year-on-year increase in freight volume and container throughput, the average ship clearance time also rose from 7 hours to 8–10 hours, indicating that operational growth is not supported by administrative efficiency. The study proposes three strategic solutions: development of a unified Single Submission Platform, institutional coordination through joint task forces, and capacity building for digital literacy among port workers.